Transition of young adults with metabolic bone diseases to adult care - Ross, Jordan; Bowden, Michelle R.; Yu, Christine; Diaz-Thomas, Alicia (Frontiers in Endocrinology, 2023)
As more accurate diagnostic tools and targeted therapies become increasingly available for pediatric metabolic bone diseases, affected children have a better prognosis and significantly longer lifespan. With this potential for fulfilling lives as adults comes the need for dedicated transition and intentional care of these patients as adults. Much work has gone into improving the transitions of medically fragile children into adulthood, encompassing endocrinologic conditions like type 1 diabetes mellitus and congenital adrenal hyperplasia. However, there are gaps in the literature regarding similar guidance concerning metabolic bone conditions. This article intends to provide a brief review of research and guidelines for transitions of care more generally, followed by a more detailed treatment of bone disorders specifically. Considerations for such transitions include final adult height, fertility, fetal risk, heritability, and access to appropriately identified specialists. A nutrient-dense diet, optimal mobility, and adequate vitamin D stores are protective factors for these conditions. Primary bone disorders include osteogenesis imperfecta, hypophosphatasia, and X-linked hypophosphatemic rickets. Metabolic bone disease can also develop secondarily as a sequela of such diverse exposures as hypogonadism, a history of eating disorder, and cancer treatment. This article synthesizes research by experts of these specific disorders to describe what is known in this field of transition medicine for metabolic bone diseases as well as unanswered questions. The long-term objective is to develop and implement strategies for successful transitions for all patients affected by these various conditions.